1998
DOI: 10.1038/sj.ijo.0800580
|View full text |Cite
|
Sign up to set email alerts
|

Influence of duration of obesity on the insulin resistance of obese non-diabetic patients

Abstract: OBJECTIVE: To investigate whether duration of obesity has an independent impact on insulin resistance. DESIGN: Case-control study. SUBJECTS: 30 non-diabetic obese subjects (age, 34 AE 2 y, body mass index (BMI), 33.5 AE 0.8 kg Á m 72 ) with a range (1±35 y) of self-reported duration of obesity, and 12 age-and gender-matched non-obese controls (BMI, 22.1 AE 0.6 kg Á m 72 ). MEASUREMENTS: Oral glucose tolerance (40 g Á m 72 ), insulin sensitivity (by the euglycaemic insulin clamp technique), and insulin secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 21 publications
1
25
2
2
Order By: Relevance
“…In contrast with these findings, it has been reported that an early onset of obesity is associated with higher insulin sensitivity. 5,43 No well-defined adaptative mechanisms have been evoked to explain this surprising result, which, differently from the study by Janssens et al, 42 has been obtained in a very small sample (17 subjects in the study by Brochu et al 5 and 30 in the study by Muscelli et al…”
Section: Natural History Of Obesitycontrasting
confidence: 52%
“…In contrast with these findings, it has been reported that an early onset of obesity is associated with higher insulin sensitivity. 5,43 No well-defined adaptative mechanisms have been evoked to explain this surprising result, which, differently from the study by Janssens et al, 42 has been obtained in a very small sample (17 subjects in the study by Brochu et al 5 and 30 in the study by Muscelli et al…”
Section: Natural History Of Obesitycontrasting
confidence: 52%
“…Although most studies of obesity duration point to greater cardiovascular risks for those with longer-standing obesity, including higher risks of dyslipidemia, others have found an equivocal 20 or, as suggested by our data, a negative association 21 between obesity in younger years and hyperlipidemia later in life. This finding of a possible protective effect of adolescent obesity on development of high level of LDL cholesterol later in life is enigmatic at present.…”
Section: Discussionmentioning
confidence: 43%
“…19 In a comparison of obese individuals with lean individuals, insulin action was inversely associated with serum UA. 18 A large Italian study also reported a negative correlation between hyperuricemia and insulin action. 17 The relationship between UA and an increased risk for development of T2DM has also been found in larger studies.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] In one study, serum triglycerides and insulin action together explained 50% of the variation in serum UA level in a group of 37 subjects. 19 In a comparison of obese individuals with lean individuals, insulin action was inversely associated with serum UA.…”
Section: Discussionmentioning
confidence: 99%